2015
DOI: 10.1002/ccd.26299
|View full text |Cite
|
Sign up to set email alerts
|

Early healing assessment with optical coherence tomography of everolimus‐eluting stents with bioabsorbable polymer (synergy™) at 3 and 6 months after implantation

Abstract: The everolimus-eluting stent with absorbable polymer, Synergy™, is associated to a high degree of intimal coverage and apposition at 3 months after implantation with additional increase at 6 months. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…With the assumption of an average Angiolite stent length of 20 mm, a mean number of eight struts per analyzed cross‐sectional frame, and a 0.5 mm stepping interval for OCT analysis, we estimated to have 8,000 analyzable struts for 3‐month analysis and a further 8,000 struts analyzable at 6‐month analysis if n = 75 patients were to be enrolled (25 patients and 50 patients scheduled for 3‐ and 6‐month OCT follow‐up, respectively). On the basis of the recent published OCT data evaluating stent healing characteristics , we empirically chosed to enroll 75 patients (potentially yielding 24,000 struts for analysis). Assuming a 20% loss to imaging follow‐up rate, we thus planned to enroll a minimum of 100 patients.…”
Section: Methodsmentioning
confidence: 99%
“…With the assumption of an average Angiolite stent length of 20 mm, a mean number of eight struts per analyzed cross‐sectional frame, and a 0.5 mm stepping interval for OCT analysis, we estimated to have 8,000 analyzable struts for 3‐month analysis and a further 8,000 struts analyzable at 6‐month analysis if n = 75 patients were to be enrolled (25 patients and 50 patients scheduled for 3‐ and 6‐month OCT follow‐up, respectively). On the basis of the recent published OCT data evaluating stent healing characteristics , we empirically chosed to enroll 75 patients (potentially yielding 24,000 struts for analysis). Assuming a 20% loss to imaging follow‐up rate, we thus planned to enroll a minimum of 100 patients.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, only one study has to date provided OCT data in 40 patients 3 and 6 months post SYNERGY stent implantation. 22 In this two-centre non-randomised Spanish study, the proportion of uncovered but apposed struts was 2.5% and 1.9% in the 3-month and 6-month group (P=0.03) and the proportion of uncovered and malapposed struts was 3% and 1.8%, respectively (P<0.001). An experimental study in atherosclerotic swines previously showed a very low degree of parastrut inflammation 30 days after implantation of the device.…”
Section: Discussionmentioning
confidence: 75%
“…However, in the present study, three stent groups already had about 80% strut coverage, which might indicate a good healing response in strut coverage. In fact, in several studies that investigated patients at 3 months after PCI, the healing outcome of these three stent types was improved [ [27] , [28] , [29] , [30] , [31] ]. Herein, there was no significant difference in OFDI findings and CAS findings, except for PLIA on OFDI.…”
Section: Discussionmentioning
confidence: 99%